Effect of slaking on hydraulic properties of waste materials at the Mae Moh Mine, Thailand - Sruti, Nadia Zaman; Kuo-Chieh Chao; Noppadol Phien-Wej; Avirut Puttiwongrak; Local Government Engineering Department (LGED), Bangladesh (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Slope instability may arise due to the gradual deterioration and weathering of the materials that form the slope, which can be attributed to changes in temperature or slaking over an extended period. In recent years, a large slope failure occurred in a spoil dumping area in Mae Moh Mine, Thailand. Forensic investigations into the incident concluded that the failure was caused by the deterioration or slaking of waste materials which formed into clay layer over time. Previous research on the site also conducted that UB and Red Bed have a greater tendency for slaking, which may have been the primary cause of the failure. The slaking could also affect the hydraulic property of these waste materials. The collected waste materials i.e., OB, IB, UB and Red bed claystones are tested in the laboratory for constant head permeability tests and filter paper & Wp4c tests for determining soil water characteristics curve for freshly collected samples. Some samples went through the wet and dry cycle for slaking. After slaking the slaked samples are tested constant head permeability test and filter paper & Wp4c tests for the soil water characteristics curve. The permeability test results show that for the fresh sample, the hydraulic conductivity is higher than the slaked samples for all types of claystones. Soil water characteristics curve also determines for the fresh and slaked samples both filter paper and Wp4c machine testing. The slaked samples show a different shape curve than the fresh sample. As the slaked particles are finer it has a lower SWCC curve than the fresh samples. Therefore, slaking affects the permeability and soil water characteristics of the waste materials. Seepage and slope stability analyses have been done to find out the factor of safety changes due to the changes in the permeability and soil water characteristics of the fresh and slaked materials. In the analyses performed by GeoStudio software, laboratory test results are used as a hydraulic boundary condition. The seepage and slope stability model shows a slightly lower factor of safety for the lower hydraulic conductivity and SWCC for the slaked samples than the fresh samples.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Geotechnical and Earth Resources Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Coal mines and mining -- ThailandWaste disposal; Mineral industries -- Waste disposal -- Thailand